Elevation of serum soluble E-selectin and VCAM-1 in severe asthma - Agnes Hamzaoui; Jamel Ammar; Fethi El Mekki; Olfa Borgi; Hédia Ghrairi; Mounira Ben Brahim; Kamel Hamzaoui (Mediators of Inflammation)
Objective: To investigate the significance of circulating adhesion molecules associated with leucocyteendothelial cell interactions in asthma, serum levels of soluble E (sE)-selectin, soluble P (sP)-selectin, soluble L (sL)-selectin, and soluble vascular cell adhesion molecule-1 (sVCAM-1) were measured in mild, moderate and severe asthma.